Presepsin as a marker of sepsis in oncological patients after surgical interventions - N. K. Guskova; A. A. Morozova; D. A. Rozenko; A. V. Alyoshkina; A. M. Skopintsev; O. N. Selyutina; N. V. Golomeeva; E. A. Guskova; A. K. Donskaya; I. V. Tselishcheva; A. S. Nozdricheva (Южно-Российский онкологический журнал, 2022)
Purpose of the study. Analysis of the possibility of using presepsin in the early diagnosis of sepsis in cancer patients after extensive surgical interventions for tumors of the thoraco-abdominal localization.Materials and methods. The study included 27 people: 10 healthy individuals (control) and 17 patients who received surgical treatment at the National Medical Research Center of Oncology for malignant neoplasms of thoraco-abdominal localization. In the blood of all patients, studies of sepsis markers were performed: presepsin (P-SEP), highly sensitive CRP (hsCRP) (PATHFAST, Japan), procalcitonin (PCT), interleukin 6 (IL6) (Cobas e 411, Germany), as well as lactate, total leukocyte count (WBC) with a leukocyte formula, a blood culture test for suspected septic complications included in a routine examination. The studies were carried out before and on the 2nd day after the operation. Data were assessed by comparing P-SEP levels with hsCRP, PCT, IL6, lactate, WBC, blood culture test results, and the clinical status of patients. Depending on the data obtained, 2 groups were distinguished: I – patients with confirmed sepsis (3 people), II – without sepsis (14 people). Statistical processing was performed using STATISTICA 13.0.Results. In the control group, the level of P-SEP was 182.7 ± 11.9 pg/ml. In patients before surgery, the marker values were 213.7 ± 47.7 pg/ml, which did not differ statistically from the control data and did not go beyond the reference values, as did the content of PCT, hsCRP, IL6. On the 2nd day after surgery, all patients showed unidirectional changes, characterized by an increase in the levels of the studied parameters, but with varying degrees of intensity. The most significant was the increase in the concentration of presepsin. At the same time, it was noted that the level of presepsin on the 2nd day after surgery in patients of group I patients with confirmed sepsis averaged 2577.5 ± 1762.5 pg/ml with a maximum level 4340.0 pg/ml, and in group II with In the absence of confirmed bacteremia, there was an increase in the level of presepsin 1205.0 pg/ml. The data obtained correlated with the dynamics of changes in the concentration of other sepsis markers – hsCRP, PCT, IL6. Thus, the study of the level of presepsin, along with widely used markers – hsCRP, PCT, IL6, allows diagnosing sepsis in the early postoperative period in cancer patients.Conclusion. In patients with malignant neoplasms of thoracoabdominal localization, changes in the levels of sepsis markers in the early postoperative period can be used as a basis for prescribing antibiotic therapy. Presepsin may be recommended for use as an early marker of sepsis in patients with oncological pathology.